Síntese e caracterização de vidros germanatos contexto óxidos de tântalo para dispositivos Luminescentes - Pietro, Gabriele Matinatti De (2014)
In this work, germanate glasses containing potassium oxide K2O and increasing amounts of tantalum oxide Ta2O5 were prepared by the melt-quenching method using melting temperatures between 1300°C and 1600°C in platinum crucibles. Two series were firstly tested in the ternary system: the first series with the same K2O and Ta2O5 content represented by (100-2x)GeO2-xTa2O5-xK2O and the second one with a constant K2O content of 10 mole% represented by (90-x)GeO2-xTa2O5-10K2O. The resulting glasses were characterized by X-ray diffraction and thermal analysis (DSC) in order to identify the glassy nature of the prepared materials as well as their thermal behavior in function of composition. These results allowed to define the second series with fixed K2O content as the most promising for optical glass-ceramics and was selected for further characterizations in this work. Spectroscopic studies by FTIR and Raman also allowed relating structural changes with variation in the glass composition and Ta2O5 concentration. The results suggest that Ta is inserted into the covalent germanate network and acts as a glass intermediary. Crystallization studies performed at characteristic temperatures previously determined from thermal analysis allowed identifying the preferential precipitation of nanosized Ta2O5. Luminescence of Eu3+-doped glass samples in the visible was also helpful to relate small variation in Eu3+ symmetry as a function of the Ta2O5 glass concentration. However, luminescence studies of codoped Er3+/Yb3+ glass samples in the near infrared exhibited important changes with respect to the composition with respect to the increased emission bandwidth around 1,5μm as well as a decrease of the experimental lifetime of the excited state 4I13/2 for higher Ta2O5 concentrated samples.